Effect of components on the curing of glycidyl azide polymer spherical propellant through rheological method. Issue 10 (24th October 2018) - He, Liming; He, Wei; Ma, Zhongliang
Abstract : We have conducted a novel study of the influence of energy components (RDX, AP and CL-20) on curing kinetics of glycidyl azide polymer (GAP) spherical propellant based on rheological method. The autocatalytic model was used to describe curing kinetics and the parameters were determined by the model-fitting method. It was found that the incorporation of components hinders the cross-linking reaction of GAP spherical propellant. Integral isoconversional method was used on rheological kinetics to investigate the changes of the activation energy and we confirmed that the incorporation of components increased the activation energy. It was also found that such components had no effect on the trend of activation energy curves but shrank the peak value at a = 0.2. Dynamic mechanical analysis (DMA) showed the differences between pure curing system and its components. These findings are potentially helpful to control the curing effectively and optimize the processing schedules. The addition of components decreased α translation temperature which means the reduction in cross-links. The differences in the values of loss factor tan δ and β translation showed that pure curing system has lower resistance for side chain to motion.